Plasma fibrin clot phenotype independently affects intracoronary thrombus ultrastructure in patients with acute myocardial infarction - Zalewski, Jaroslaw; Bogaert, Jan; Sadowski, Marcin; Woznicka, Olga; Doulaptsis, Konstantinos; Ntoumpanaki, Maria; Zabczyk, Michal; Nessler, Jadwiga; Undas, Anetta (Thrombosis and Haemostasis, 2015)
Determinants of intracoronary thrombus (ICT) composition in patients with ST-elevation myocardial infarction (STEMI) are largely unknown. We sought to investigate whether plasma fibrin phenotype and platelet reactivity affect ICT ultrastructure. We assessed the content of fibrin, platelets and erythrocytes including polyhedrocytes by scanning electron microscopy on the surface and inside ICT aspirated from 80 STEMI patients within 12 hours since chest pain onset. Plasma fibrin clot permeability (Ks), which indicates the average pore size, lysis time (t50 %), platelet reactivity index (PRI) and ADP-induced platelet aggregation (ADP5,20μM) were evaluated on admission. All patients received aspirin and 45 (56.3 %) 600 mg of clopidogrel, 80 (60–120) min prior to aspiration. Higher content of fibrin (61.6 vs 34.3 %, P< 0.0001) and platelets (8.2 vs 4.8 %, P=0.018) and lower erythrocyte content (15.8 vs 42.9 %, P< 0.0001) were found on ICT surface compared with its inner part. After adjustment for fibrinogen, in both ICT parts fibrin content was correlated with Ks (r≤-0.55, P< 0.0001) and t50% (r≥ 0.29, P≤ 0.02) but not with PRI and ADP5,20μM. Polyhedrocytes were observed in 16 (20 %) patients and their large amount expressed as ≥ 50 % fields of view covered by polyhedrocytes was associated with the lower PRI values (40 vs 69 %, P=0.015), but not Ks or t50%. By multivariate regression, Ks (β=-0.62, P< 0.0001), clopidogrel pretreatment (β=-0.36, P< 0.001), ischemia time (β=0.19, P=0.044) and family history (β=0.18, P=0.049) independently predicted fibrin content in the whole ICT (R2=0.65, P< 0.0001). Formation of denser plasma fibrin clots is independently associated with high fibrin content within the ICT in STEMI.
Keywords: Myocardial infarction; coronary thrombosis; fibrin; platelets; scanning electron microscopy